Card tricks get started in a new craft with easy-to-follow projects for beginners - Devereux, Eve (Edison, N.J. : Chartwell Books, 1996)
Card tricks begins with an introductory section of basic techniques that will teach you the secrets of sleight of hand: how to shuffle, palm, pass, force a card, and how to make your cards fly.
"A Quintet book"--T.p. verso.
Keywords: Card tricks. -- Juvenile Literature